Operational Efficiency through Service Integration: Insights from Platform-Based Business Models (International Journal of Engineering and Computer Science, 2021)
Today's organizations are grappling with pressing issues related to efficiency. The public sector is innovating, adopting strategies and practices used by the private sector in its relentless quest for a delicate balance between costs and innovation. The private sector, on the other hand, has been challenged to generate profitable growth by questioning the conventional operating income equation of increased revenues less increased expenses, exploring how revenue lines can be enhanced without linearly increasing the corresponding expenses. This exploration is being escalated by the advances in digital technologies. I discuss these issues in the context of service provision, drawing insights from platform-based business models. I propose the concept of "service integration" to characterize the unique capabilities these business models create and apply in the service provider's advantage - enhanced selection and curation of services on offer; seamless on-demand aggregation and integration of complementary services; omnipresent use of service-related data to provide personalized, predictable and pre-emptive service experiences; establishment of trust through providing and demanding quality commitments from servitized businesses and increased scope for accelerators which boost the returns from services, especially in the case of businesses which are "servitized" using platform-based business models. By asking the question, "How well can a business integrate services that consumers or companies need?", I establish a framework to interpret a business' ability to maximize service integration en-cashable consumer value. I conclude with a look at the broader implications and challenges of service integration.